Primary health care: what is its relevance to the COVID-19 pandemic? (Research, Society and Development, 2021)
This work aims to identify and highlight the importance of the role of multidisciplinary teams in Primary Health Care (PHC) in preventing the spread of the pandemic caused by COVID-19. This is a bibliographic research in which online databases were used: SciELO and Academic Google. Thus, articles that contemplated the objectives and approaches of PHC were selected, using keywords such as the terms: “Primary Health Care”, “Basic Health Unit” and “COVID-19”. In the inclusion criteria, national researches were prioritized, as well as researches published between 2017 and 2020. In this way, the potential of actions already carried out before the pandemic with the main risk groups was highlighted, however this new context required new approaches in assistance to health care for the population of each location, such as the use of technologies to facilitate appointment scheduling and even teleconsultations, with renewal of medication prescriptions. Among the main factors, the attention and constant monitoring of the main groups at risk and the development of alternatives to respect preventive measures of social isolation, as well as the application of measures to protect and prevent the health of health professionals, stood out.